Architecture in formation : on the nature of information in digital architecture - Lorenzo-Eiroa, Pablo; Sprecher, Aaron (London : Routledge, 2013)
'Architecture in Formation is the first digital architecture manual that bridges multiple relationships between theory and practice, proposing a vital resource to structure the upcoming second digital revolution. Sixteen essays from practitioners, historians and theorists look at how information processing informs and is informed by architecture. Twenty-nine experimental projects propose radical means to inform the new upcoming digital architecture'--Publisher's website.
Includes bibliographical references and index.
Keywords: Architecture and technology; Architecture -- Information technology; Architecture -- Computer-aided design; Architecture and technology -- Designs and plans